The Effect of Various Salinity Level on the Growth and Characterization of Dunaliella sp Isolated from Jepara Waters - Endang Kusdiyantini; Triwibowo Yuwono; Joedoro Sudarsono; Hermin Pancasakti Kusumaningrum (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2004)
Dunaliella adalah salah satu biota dengan kandungan β-carotene cukup tinggi. Upaya optimalisasi produksi bcarotene pada Dunaliella berhadapan dengan beberapa masalah kultivasi, untuk mendapatkan species yang paling potensial. Hal ini terkait dengan keterbatasan pengetahuan karakteritik ecophysiologi. Alga hijau Dunaliella diketahui dapat tumbuh pada media dengan kandungan garam yang cukup tinggi, namun karena pemahaman characteristik yang keliru dapat menyebabkan identifikasi yang salah pada satu species dalam genus Dunaliella. Kultur laboratoris pada media microcosms berdasarkan salinitas telah dilakukan untuk mengetahui tingkat pertumbuhan dan karakterisasi Dunaliella sp. dari perairan Jepara. Hasil pengamatan menunjukkan bahwa Dunaliella sp. dapat beradaptasi pada salinitas 0 sampai dengan 30 ‰. Berdasarkan kepada perubahan warna pigmen Dunaliella sp. yang tidak menjadi merah pada media pemeliharaan sampai dengan 25 ‰, maka jenis yang dijumpai di Jepara mempunyai karakter dan secara taksonomis berafiliasi dengan Dunaliella viridis.Kata kunci: Dunaliella sp, Salinity, Growth, CharacterizationDunaliella is one the most enriched β-carotene eucaryotic organism known. The attempt to optimize bcarotene production from Dunaliella has faced with several problems related to its growth management,which was suspectedly unable to meet the needs of the cultured species. This is primarily because the ecophysiological characteristic affecting growth of Dunaliella have not been sufficiently understood. It wasknown that the halophilic species of the green alga Dunaliella was grown in concentrated salt solutions, but based on this characterization, some misnamed of species in genus Dunaliella also have arisen due to wrongcharacterization understanding. Laboratory cultures and mixed-species microcosms were used to asses the growth and characterization of Dunaliella sp. from Jepara Coastal Region with special emphasis on the several factors that affecting growth of organisms including salinity. The result showed that Dunaliella sp. could adapted to a variety of salt concentration from as low as 0.0 % to salt saturation of about 30 ‰. Based on its pigment colour that Dunaliella sp. doesn’t turn red in the growth on salinities up to 25 ‰, it can be characterized and affiliated taxonomically as Dunaliella viridis.Key words: Dunaliella sp, Salinity, Growth, Characterization